Prevalence of Cilioretinal Arteries: A systematic review and a prospective cross‐sectional observational study. Issue 3 (24th August 2020) - Schneider, Miklos; Molnar, Adel; Angeli, Orsolya; Szabo, Dorottya; Bernath, Fruzsina; Hajdu, Dorottya; Gombocz, Eszter; Mate, Balint; Jiling, Balint; Nagy, Balazs Vince; Nagy, Zoltan Zsolt; Peto, Tunde; et al.
Abstract: Purpose: To review studies focusing on cilioretinal arteries (CLRA) in order to assess the overall prevalence and establish the prevalence of CLRA in a Hungarian Caucasian population. Methods #1: Systematic literature review of published studies with at least 100 participants. Methods #2: Non‐mydriatic digital colour photographs were taken of 1000 consecutively enrolled healthy Caucasian young adult volunteers. Images were graded by two trained independent observers. Number and location of identified cilioretinal arteries were recorded and statistically analysed. Results #1: Prevalence of CLRA ranges from 6.9% to 49.5%. Detection with fluorescein angiography yields the highest values followed by fundus photography and ophthalmoscopy. Unilateral presence of CLRA is between 70.30% and 93.65%, and temporal location is between 80.77% and 100%. Results #2: We found at least one CLRA in 36.5% of the participants and in 22.75% of all the examined eyes. Cilioretinal arteries (CLRA) were unilateral in 75.34% and bilateral in 24.66%. Of all the identified CLRA, 96.16% were originating from the temporal rim of the optic disc. We identified at least one temporal CLRA supplying the macula in 28% of the participants and 16.95% of the examined eyes. Conclusion: Prevalence of CLRA varies depending on identification method. Unilateral presence is unequivocally more frequent similarly to temporal location. From a risk of bias standpoint, high‐quality studies are rare. Our data on the distribution pattern of CLRA are similar to that in the international literature. Based on our findings, we assume that slightly more than one‐third of the Hungarian Caucasian population has a CLRA.